TYRE WEAR DURING BRAKING - Janićijević, Nenad (Journal of Applied Engineering Science, 2015)
Apart from the other factors, a tyre wear is primarily dependent on energy absorbed within the tyre grip area during braking or during vehicle acceleration. This paper shows set of derived equations that can be used to calculate the amount of absorbed energy within brakes, as well as within the tyre grip area for various typical cases and conditions occurring during braking.
Keywords: Wear; Tyre; Vehicle; Braking; Energy balance